Penerapan Pendidikan Karakter dan Penerapannya Perspektif Hadis Tarbawi - Mualana Azizi Nasution; Chaerul Anwar; Ahmadi Usman (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2021)
A person's character is the process of how parents choose a life partner until they are born into the world and then associate with their environment. Good character is a process of journey from time to time that needs to be taught from childhood to growing up. The purpose of this research is to examine how the concept of character education, types of character education and its application of the hadith tarbawi perspective with the hope that parents, educators, and students can understand, understand, and implement the concept of character education taught by the Prophet Muhammad based on the hadiths that have been narrated from various schools of thought through the practice of faith, disrespect and discipline in order to create a character with noble character, noble character, and love one another. In addition, this research can change the perspective and thinking of parents and teachers in educating children through the sunnah of the Prophet SAW through the teachings of Islamic law which have been clearly described and strengthened by the Al-Qur'an.